Unstimulated and glucose-stimulated ghrelin in depressed patients and controls. (June 2014) - Paslakis, Georgios; Westphal, Sabine; Hamann, Bettina; Gilles, Maria; Lederbogen, Florian; Deuschle, Michael
Introduction: The neuropeptide ghrelin stimulates hunger and weight gain. Ghrelin actions have been associated with depression in a number of preclinical and clinical studies, although some studies comparing basal peripheral ghrelin levels between depressed patients and controls found no differences between the groups. Methods: Twenty patients with a melancholic depressive episode and 15 controls received a 75 g glucose load and ghrelin levels were measured at 0, 30, 60 and 90 min after the beginning of the test. The patients were then either treated with mirtazapine ( n =10) or venlafaxine ( n =10) and underwent the same procedure (glucose load and ghrelin assessment) after four weeks of treatment. Results: Basal ghrelin concentrations did not differ between patients and controls, although the ghrelin responses following the glucose load were lower in patients and differed significantly to the controls' responses. After treatment, the patients' ghrelin responses to the glucose load increased by trend and approximated those in the control group. Conclusion: Ghrelin is involved in appetite-regulating pathways during depression. For the first time we show that a functional test procedure using a standardised glucose load is more suitable than the assessment of basal peripheral ghrelin levels to detect differences between diagnostic groups.